2009
DOI: 10.1002/ccd.21816
|View full text |Cite
|
Sign up to set email alerts
|

Multidetector CT coronary angiography for patient triage to invasive coronary angiography: Performance and cost in ambulatory patients with equivocal or suspected inaccurate noninvasive stress tests

Abstract: MDCTA shows excellent performance as a triage for invasive angiography in patients with stress tests that are equivocal or thought inaccurate. A negative CTA confers good 12-month prognosis. Substantial cost savings may accrue using MDCTA in this triage role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 12 publications
(17 reference statements)
1
7
0
Order By: Relevance
“…The abstract or full text of the 39 remaining studies were evaluated to determine eligibility. Twenty-one studies (14,15,23,25,28,(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56) were excluded after further review for reasons outlined in Figure 1. Eighteen studies were identified for inclusion from the literature search (7,8,10 -12,16 -22,24,26 -30).…”
Section: Resultsmentioning
confidence: 99%
“…The abstract or full text of the 39 remaining studies were evaluated to determine eligibility. Twenty-one studies (14,15,23,25,28,(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56) were excluded after further review for reasons outlined in Figure 1. Eighteen studies were identified for inclusion from the literature search (7,8,10 -12,16 -22,24,26 -30).…”
Section: Resultsmentioning
confidence: 99%
“…As previously mentioned, the application of current investigation algorithms in "real-world" clinical practice results in a large number of ICAs that do not demonstrate any significant coronary obstruction and, thus, do not lead to any therapeutic intervention (1). The results of 2 recent studies suggest that the strategy of using coronary CTA as a gatekeeper to ICA could be cost saving in patients with equivocal noninvasive stress tests (17,18). Accordingly, the ACCF/SCCT/ACR/AHA/ASE/ ASNC/SCAI/SCMR 2010 Appropriate Use Criteria for Cardiac Computed Tomography (12) defined the use of coronary CTA in patients with equivocal or discordant stress tests as an appropriate indication.…”
Section: Discussionmentioning
confidence: 99%
“…1 The few available studies suggest that this may be a cost-effective strategy, with up to a 4-fold reduction in costs driven by reductions in unnecessary invasive coronary angiography 77,78 ; however, these are limited to small, single-center observational studies. 1 The few available studies suggest that this may be a cost-effective strategy, with up to a 4-fold reduction in costs driven by reductions in unnecessary invasive coronary angiography 77,78 ; however, these are limited to small, single-center observational studies.…”
Section: Coronary Cta After Equivocal or Abnormal Mpsmentioning
confidence: 99%